2010
DOI: 10.3354/ame01372
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton assemblages and characterization of a Dinophysis acuminata population during an upwelling–downwelling cycle

Abstract: The distributions of Dinophysis acuminata, its potential prey Myrionecta rubra, and the microplankton populations associated with them, were studied in Ría de Pontevedra (NW Spain) during a 2 wk cruise that covered an upwelling-downwelling cycle, and during intensive sampling over 21 h at the end of the cruise. Special attention was focused on the characterization and physiological condition of D. acuminata. There was vertical segregation between a phytoplankton assemblage that was dominated by upwelling-promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 32 publications
3
15
0
Order By: Relevance
“…Together, these results suggest that prey availability influenced the total amount of OA, DTX1, and PTX2. This finding is in agreement with previous reports on other species of Dinophysis in the field and in culture (Kim et al , 2008; Riisgaard and Hansen, 2009; Campbell et al , 2010; Gonzalez-Gil et al , 2010; Minnhagen et al , 2011; Sjoqvist and Lindholm, 2011; Hattenrath-Lehmann et al , 2013), that reported maximum abundances of Dinophysis spp. occurring shortly after the peak and subsequent depletion of prey.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Together, these results suggest that prey availability influenced the total amount of OA, DTX1, and PTX2. This finding is in agreement with previous reports on other species of Dinophysis in the field and in culture (Kim et al , 2008; Riisgaard and Hansen, 2009; Campbell et al , 2010; Gonzalez-Gil et al , 2010; Minnhagen et al , 2011; Sjoqvist and Lindholm, 2011; Hattenrath-Lehmann et al , 2013), that reported maximum abundances of Dinophysis spp. occurring shortly after the peak and subsequent depletion of prey.…”
Section: Discussionsupporting
confidence: 94%
“…The vertical distribution of Dinophysis extends to as deep as 110 m (Fux et al , 2010) ranging from the surface to below the euphotic zone (Gisselson et al , 2002), suggesting that the genera are tolerant of high and low light conditions. Dinophysis growth is often associated with a stable water column (Maestrini, 1998; Seeyave et al , 2009; Reguera et al , 2012) and cells have often been shown to accumulate in thin layers or patches due to horizontal and vertical migration, transport driven by wind or currents (Mackenzie, 1991, 1992; Xie et al , 2007), or biological behavior to locate prey or avoid predators (Maestrini, 1998; Campbell et al , 2010; Gonzalez-Gil et al , 2010; Sjoqvist and Lindholm, 2011, Hattenrath-Lehmann et al , 2013). Populations have also been documented within systems containing a range of ambient dissolved nutrient levels: total dissolved nitrogen, 2 – 21 µM; silicate, 0 – 10 µM, and phosphate, 0 – 0.24 µM (Delmas et al , 1992; Maestrini, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Culture experiments have also shown the relationship between an ample supply of prey and high division rates in Dinophysis [24,26]. In field populations, Dinophysis may be subject to prey limitation most of the time and peak densities are preceded by or co-occur with high densities of Mesodinium [18,27]. Furthermore, D. acuminata and Mesodinium rubrum were observed exhibiting similar diurnal vertical migrations in a 24-h study under stratified conditions in Ría de Vigo [28], and thin layers of the dinoflagellate and the ciliate co-occurred in time, but not always in space, in a coastal inlet in the northern Baltic Sea [29].…”
Section: Discussionmentioning
confidence: 99%
“…would be often preylimited due to the scarcity of prey and would receive a large fraction of its carbon requirements from photosynthesis. Field observations confirm a high variability in the frequency of vacuolated cell-the unambiguous sign of recent phagotrophic feeding-in Dinophysis populations Gonzá -lez-Gil et al, 2010). Nevertheless, correlation of Dinophysis and M. rubrum abundances has to be interpreted with care, because patches of the respective populations may meet offshore, far from the sampling areas, and once the Dinophysis cells are satiated, they can undertake several divisions in the absence of Mesodinium.…”
Section: In Situ Growth: Slow Growers or Amazing Survivors?mentioning
confidence: 93%